ANALISIS PERSEPSI INVESTOR MUSLIM TERHADAP SAHAM SYARIAH - Ardiansyah; Azhar (Jurnal Syariah dan Ekonomi Islam, 2025)
This study aims to analyze the factors influencing Islamic investment decisions in Indonesia. A quantitative approach with descriptive and explanatory methods was applied to objectively measure relationships between variables. Data were collected through online questionnaires distributed to individuals who have invested or are interested in Islamic financial instruments. The findings show that Muslim investors’ behavior is influenced by ethical values, religiosity, motivation, and investment patterns. Moreover, return and risk are the main considerations in making investment decisions. Trust in Islamic financial institutions and financial literacy also play significant roles in shaping investors’ confidence and interest in Sharia-compliant products. These findings are expected to contribute to the development of a more inclusive, sustainable, and Sharia-based Islamic capital market.